Impact of Morphological Status on Long-Term Outcome Among Patients Undergoing Liver Surgery for Intrahepatic Cholangiocarcinoma - Bagante, F (2019)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2019-03-20T16:33:26Z No. of bitstreams: 1 Ann Surg Oncol 2017 2491.pdf: 547793 bytes, checksum: 09d80d60942f38d63fadfc75da1a9344 (MD5)